1960
DOI: 10.1038/icb.1960.29
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Innate Resistance of Mice to Infection With Mousepox

Abstract: SUMMARY Strains of mice differ greatly in their susceptibility to mousepox. The highly resistant strain C57 Bl has been compared with a susceptible strain of mice with regard to virus growth and antibody production. Differences in virus growth in the two strains of mice appeared at a certain stage of the infection, which was the time at which neutralizing antibody was demonstrable in the blood of resistant mice. Neutralizing antibodies, active immunity and hypersensitivity were shown to appear at least a day e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1962
1962
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…It may be significant, however, that in preliminary studies Blandford (6) showed that C3H mice developed more glomerular Sendai immunoglobulin deposits than did C57BL mice and that Fl (C3H x C57BL) hybrids were intermediate. Also, C57BL/6 mice that are more resistant to Sendai virus infection also are highly resistant to tumor induction by polyoma virus (17) and to mouse poxvirus infection (29,30), and in both latter cases the resistance is due likely to either an aggressive humoral or cellular immune response (3,29,30). In addition, Sendai virus-sensitive DBA/2 mice are more susceptible than Sendai virus-resistant C57BL mice to induction of polyoma tumors (16), which is thought to result from earlier development of cellular immune response in C57BL mice (17).…”
mentioning
confidence: 99%
“…It may be significant, however, that in preliminary studies Blandford (6) showed that C3H mice developed more glomerular Sendai immunoglobulin deposits than did C57BL mice and that Fl (C3H x C57BL) hybrids were intermediate. Also, C57BL/6 mice that are more resistant to Sendai virus infection also are highly resistant to tumor induction by polyoma virus (17) and to mouse poxvirus infection (29,30), and in both latter cases the resistance is due likely to either an aggressive humoral or cellular immune response (3,29,30). In addition, Sendai virus-sensitive DBA/2 mice are more susceptible than Sendai virus-resistant C57BL mice to induction of polyoma tumors (16), which is thought to result from earlier development of cellular immune response in C57BL mice (17).…”
mentioning
confidence: 99%
“…Newborn mice of the resistant strain are apparently not resistant when 1-2 days old or at 8-12 months. High resistance was found at 4 8 weeks of age (Schell, 1960).…”
Section: Ontogeny Of Resistancementioning
confidence: 91%
“…The virus grows throughout the mouse in a large variety of tissues, including lymph node and liver, but it is not known whether macrophages are selectively affected. The virus grows equally well in monolayers of mouse fibroblasts from both strains (Schell, 1960).…”
Section: H Mousepoxmentioning
confidence: 94%
See 1 more Smart Citation
“…This host-virus interaction has been examined extensively in mice and reported to be under the control of a single dominant gene (BANG and W AR-WICK 1960;CHANG and HILDEMANN 1964;GOODMAN and KOPROWSKI 1962 a, b;LINDENMANN et al 1978;MOGENSEN 1977;SABIN 1952;SCHELL 1960;OLDSTONE et al 1973) or due to a multigenic complex (CHESEBRO et al 1974;LILLY and PINCUS 1973;LOPEZ 1975;LOPEZ and DUDAS 1979;YooN and NOTKINS 1976). This host-virus interaction has been examined extensively in mice and reported to be under the control of a single dominant gene (BANG and W AR-WICK 1960;CHANG and HILDEMANN 1964;GOODMAN and KOPROWSKI 1962 a, b;LINDENMANN et al 1978;MOGENSEN 1977;SABIN 1952;SCHELL 1960;OLDSTONE et al 1973) or due to a multigenic complex (CHESEBRO et al 1974;LILLY and PINCUS 1973;LOPEZ 1975;LOPEZ and DUDAS 1979;YooN and NOTKINS 1976).…”
Section: H Friedman and S Spectermentioning
confidence: 99%